An integrated weed management approach in tomato using soil steaming, mulching, and winter cover crops - de Oliveira, Tabata Raissa; Serafim, Augusto Dubou; Breland, Brenton; Miller, Alyssa; Beneton, Karina; Singh, Varsha; Segbefia, Worlanyo; Argenta, Josiane C.; Broderick, Shaun R.; Tseng, Te Ming (Frontiers in Agronomy, 2023)
One of the most significant yield losses in tomato is due to weeds. Yellow and purple nutsedge, large crabgrass, and Palmer amaranth are the most troublesome weed species in tomato production throughout the southeastern United States. This study aimed to determine the impact of soil steaming, plastic mulching, and cover crops on weed suppression, tomato height, and fruit yield. The cover crops used were hairy vetch, crimson clover, and cereal rye. The study was conducted at the Mississippi State University Truck Crops Experiment Station in Crystal Springs, Mississippi, USA. The experiment used a completely randomized block design with three fall cover crop treatments, including fallow, and each was replicated three times and repeated in two years. Each plot was broadcasted with a mixture of yellow nutsedge, large crabgrass, barnyardgrass, and Palmer amaranth at a density of 20 plants m-2 for each weed species. Two days after sowing the weed seeds, the soil surface was steamed according to its assigned treatment until it reached 61 °C for either 0, 5, or 20 min. After steaming, drip irrigation tubing was laid on each row, and three of six rows in each block were randomly assigned to be covered by black, 1-mil thick plastic mulch. Data were recorded in both years, including weed cover, plant height, and fruit yield. The lowest weed density was observed at 5 min of soil steaming in mulched treatment, and the highest density was noted at 0 min of soil steaming in the absence of mulching. Yellow nutsedge was the dominant weed species, even under steam and mulch treatments. The use of cover crops did not show a difference compared to fallow treatments. Tomato plants in steamed soil were up to 13 cm taller than those in unsteamed soils. Additionally, steaming at 5 or 20 min in combination with plastic mulch increased the marketable and cull yield. Soil steaming and mulching increased tomato plant height and yield while decreasing weed population and can, therefore, be effectively incorporated into an integrated weed management program in tomato.